2004
DOI: 10.1177/112067210401400602
|View full text |Cite
|
Sign up to set email alerts
|

Results of the Application of Intraoperative Mitomycin C in Dacryocystorhinostomy

Abstract: The authors conclude that the use of intraoperative MMC in DCR surgery does not change the success rate of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 7 publications
1
33
0
1
Order By: Relevance
“…Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10]. The success rates of these procedures vary in the range of 25-92% with the majority being under 50-60% (Table 7).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Compared with the single-stent group, no significant complications appeared, which was consistent with previous reports [11][12][13][14][15]. The other treatment methods implicated for canalicular obstruction are DCR combined with membranectomy [5,6], trephination and silicone tube stenting [7,16], ballooning with/without silicone stenting [17,18], ballooning canaliculoplasty following lacrimal trephination [8], and intraoperative use of mitomycin C [9,10]. The success rates of these procedures vary in the range of 25-92% with the majority being under 50-60% (Table 7).…”
Section: Discussionsupporting
confidence: 85%
“…For canalicular obstruction, the cause of failure is restenosis or sticky adhesive changes of the canaliculus following the removal of the silicone tube [5][6][7][8][9][10]. We reasoned that the insertion of a wider stent would make the canalicular pathway more patent and aid in maintaining the clearance of the pathway following removal of the tube.…”
Section: Introductionmentioning
confidence: 94%
“…However, limitations have been reported for both of them, including the potential of silicone intubation to induce an [18][19][20] and the inhibitory effect of MMC on fibroblasts, which potentially limits the regeneration of healthy epithelium. 27,28 Therefore, the ideal agent should promote healthy re-epithelialization without excessive scarring, to ensure ostial patency in DCR. P-values of the rates of failure resulted from the scar and granulation formation were evaluated by Fisher's exact test.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,8,9,[18][19][20] Some authors advocate the use of mitomycin C (MMC) intraoperatively to reduce fibrosis formation, [21][22][23][24][25][26] although granulation tissue has been reported to form around the ostia following MMC application during EES-DCR. 27,28 Hyaluronan is a ubiquitous polysaccharide component of the extracellular matrix. Both hyaluronan and its derivatives have been reported to reduce scarring and to promote wound healing in naso-sinal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…5 Roozitalab et al (2004) said that use of intraoperative MMC in DCR does not change success rate of this procedure. 6 Farahani et al (2008) conducted prospective doubleblind randomized clinical trial and showed that patients with nasolacrimal duct obstruction who underwent endoscopic DCR did not benefit from adjunctive topical application of MMC. 7 Although, clinically there were lesser complications in MMC group as compared to the control group but statistically they were not significant but the results were comparable to the above studies.…”
Section: Discussionmentioning
confidence: 98%